Pengaruh Gaya Kepemimpinan dan Motivasi Terhadap Kinerja Pegawai Tidak Tetap Badan Pendapatan Daerah Kabupaten Paser - Syifi Fauziyah; Istiqomah Istiqomah; Putri Sagita (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
The aim of this research is to determine the simultaneous and partial influence as well as the dominant variables of leadership style (X1) and work motivation (X2) on the performance of non-permanent employees (Y), of the Paser Regency Regional Revenue Agency. The population of this study were temporary employees of the Paser Regency Regional Revenue Agency, using a saturated sampling technique and the number of samples obtained was 47 respondents. This research questionnaire consists of 21 statements. The results of testing the research instrument, namely the questionnaire, showed that 21 statements were declared valid because r calculated > r table, namely 0.2907. Apart from that, all statements were declared reliable because the Cronbach's Alpha value was greater than 0.60 (0.884 > 0.60). The regression equation obtained is Y= 7.595 + 0.021X1 + 0.471X2. Leadership style variables (X1), work motivation (X2), have a positive influence on the performance of non-permanent employees (Y) at the Paser Regency Regional Revenue Agency. The correlation coefficient value R is 0.818, which means that the correlation relationship is very strong between leadership style (X1), work motivation (X2), and the performance of non-permanent employees (Y). The Adjusted R Square value is 0.654, which means that the independent variables, namely leadership style (X1) and work motivation (X2) can explain employee performance (Y) by 65.4%, while 34.6% is explained by other factors outside this research. The results of the F test obtained an Fcount value of 44.415 and a significant level of 0.000 and an Ftable value of 3.21 (df 2:44), so Fcount > Ftable (44.415 > 3.21) so that H0 was rejected and Ha was accepted, which means there is a simultaneous (simultaneous) influence of the leadership style variables (X1) and work motivation (X2) on the performance of non-permanent employees (Y) at the Regional Revenue Agency of Paser Regency. The results of the t test showed that the value of the Leadership style variable (X1) was 2.731 with a significant level of 0.009 and the work motivation variable (X2) was 9.313 with a significant level of 0.001, so tcount > ttable (tcount > 2.01537) so that H0 was rejected and Ha was accepted, which means there is an independent or partial influence on the leadership style variables (X1) and work motivation (X2) The highest t-count value is the work motivation variable (X2) of 9.313 which has a dominant influence on the performance of non-permanent employees (Y), at the Regional Revenue Agency of Paser Regency. so the second hypothesis is that the work motivation variable (X2) which has a dominant influence on the performance of non-permanent employees (Y) at the Paser Regency Regional Revenue Agency is proven so that the conclusion is that H0 is rejected and Ha is accepted.